Black scholars matter : visions, struggles, and hopes in Africana biblical studies - Byron, Gay L.; Page, Hugh R., Jr (Resources for biblical study, 2022)
"This book collects the presentations of twelve leading Africana scholars who participated in the groundbreaking #Black Scholars Matter virtual symposium held in August 2020 that was organized by the Society of Biblical Literature's Black Scholars Matter Task Force in coordination with the SBL's Committee on Underrepresented Racial and Ethnic Minorities in the Profession. These scholars share their perspectives on biblical studies and their experiences in the discipline on a range of topics, including blatant and subtle forms of bias and racism; mentoring; lessons of struggle, sacrifice, and lack of support; reflections on the obstacles of national tragedies, geographical locations, and academic disciplines; and the challenges of creating a more welcoming environment for the next generation of Black biblical scholars. Eight additional contributors and stakeholders that have administrative and decision-making responsibilities within theological and other settings address the need for institutional and personal accountability"--